Effects of Elliptical and Circular Nozzles on Diesel Spray Characteristics Under High Ambient Density - Qinghai Sun; Run Zou; Liangyu Li; Huan Wen; Feng Li; Wei Yang; Tiexiong Su (Applied Sciences)
In this paper, the macroscopic and microscopic characteristics of diesel spray with elliptical and circular nozzles were investigated under an ambient density of 65.6 kg/m3 by combining an optical test and numerical simulation method of VOF-Spray One-Way Coupling and Large Eddy Simulation. Two elliptical nozzles with varying aspect ratios (1.25 and 1.5) and a circular nozzle were employed for comparison, with the same cross-sectional area. The results demonstrated that the spray tip penetration (STP) of elliptical nozzles was significantly diminished in comparison to that of the circular nozzle and that STP for the elliptical nozzle with a larger aspect ratio was observed to be smaller, primarily due to the elevated aerodynamic drag and accelerated kinetic energy dissipation. The spray cone angle (SCA) of elliptical nozzles was greater than that of the circular nozzle. The average SCA of the elliptical nozzle with a larger aspect ratio was the greatest in both planes. The spray asymmetry with elliptical nozzles resulted in the instability of the spray boundary, leading to the earlier fragmentation and atomization of the spray and faster radial diffusion. For the same STP, the elliptical nozzle with a larger aspect ratio exhibited the greatest spray area in both planes. Elliptical nozzles are subject to a greater degree of inhomogeneous shear than circular nozzles, which results in an accelerated rate of droplet breakage and a concomitant decrease in Sauter Mean Diameter.